Painting with demons the art of Gerolamo Savoldo - Fried, Michael 1939- (Reaktion Books, 2021)
The achievements of Italian Renaissance painter Giovanni Gerolamo Savoldo were, even during a period of unprecedented artistry, out of the ordinary. Born in Brescia around 1480, he radically reimagined Christian subjects. His surviving oeuvre of roughly fifty paintings--from the intensely poetic Tobias and the Angel to sober self-portraits--represents some of the most profound work of the period. In Painting with Demons, a beautifully illustrated book and the first in English devoted to the painter, Michael Fried brings his celebrated skills of looking and thinking to bear on Savoldo's art, providing a stunning contribution to our understanding both of the early modern European imagination and of the achievement of this underappreciated artist.
Keywords: Savoldo, Gian Girolamo -- 1480-1548